Arah Kebijakan Pemerintah Aceh Pasca Penerapan Undang-undang Nomor 11 Tahun 2006 dalam Mewujudkan Perdamaian Positif di Aceh - fajri, nurul; Sari, Novita; Mirza Nusuary, Firdaus (Program Studi Ilmu Politik, Universitas Syiah Kuala, Banda Aceh, 2023)
AbstractThe Government of Aceh has implemented Law Number 11 of 2006 for over a decade. The expectations of the Acehnese people were that this law would improve their welfare, balance power, and involve civil society in decision-making processes. However, after three leadership periods have passed, there has been no significant improvement experienced by the community. In fact, the implementation of this law has further exacerbated vertical conflicts within Acehnese society. This research aims to analyze the policies of the Aceh Government intended to foster positive peace in Aceh. The study utilizes a qualitative descriptive method, where secondary data consists of regional government policy documents, and primary data is gathered through interviews conducted with several Aceh government institutions. Based on the research findings, the Aceh Government has not been able to achieve positive peace in Aceh. The policies implemented by the Aceh Government do not demonstrate a shift towards positive peace in Aceh. The implementation of Law Number 11 of 2006 has not been optimal in accordance with the principles of the Helsinki MoU consistently and comprehensively. The Aceh Government needs to enhance coordination and synergy with the central government to ensure effective and comprehensive implementation of Law Number 11 of 2006.Keywords: Aceh, Positive peace, UUPA (Aceh Government Law)